The Tineoidea of Kyrgyzstan with the description of Nemapogon kalliesi Gaedike, sp. n. and a list of species from adjacent countries (Lepidoptera: Meessiidae, Tineidae) - R. Gaedike (SHILAP)
Nemapogon kalliesi Gaedike, sp. n., is described from Kyrgyzstan and new country records are presented for Trichophaga ziniella Zagulajev, 1960 and Tinea bothniella Svensson, 1953. Sixteen species are now known from Kyrgyzstan. A list is given of the taxa of Meessiidae and Tineidae of Kyrgyzstan and the adjacent countries Kazakhstan, Turkmenistan, Uzbekistan, and Tajikistan.